Evaluation of Trends and Rationality in Prophylactic Antibiotic Use Among Caesarean Section Patients at a Hospital in Malang City - Andreani, Shanty; Valentina Yurina; Efta Triastuti (Pharmaceutical Journal of Indonesia, 2026)
Introduction: The caesarean section rate in Indonesia has been increasing, reaching 25.9% of total deliveries. This condition potentially increased the risk of complications, including Surgical Site Infection (SSI). Globally, the incidence of SSI in cesarean section patients ranged from 5 to 15%. Objectives: This study aimed to analyze differences in the rationality of prophylactic antibiotic used concerning body temperature and Length of Stay (LOS) in cesarean section patients at a hospital in Malang City. Methods: The study employed a retrospective design with a cross-sectional approach and applied purposive sampling. The research instruments included medical records and data collection sheets. The analysis of prophylactic antibiotic usage trends was conducted using the ATC/DDD and DU 90% methods, in accordance with the WHO guidelines. Meanwhile, the Gyssens method was used to evaluate the rationality of prophylactic antibiotic use. Results: The study results showed that the total DDD/100 patient-days was 15.5, with cefazolin classified as a prophylactic antibiotic within the DU 90% segment. Based on the Gyssens method, 183 samples (52.9%) were classified as rational antibiotic use, while 163 cases (47.1%) were classified as irrational. In terms of body temperature, no difference was found between rational and irrational antibiotic use. Similarly, regarding LOS, no significant difference was observed between these two categories of antibiotic rationality. Conclusions: Based on the study findings, It can be concluded that there is no significant difference between the rationality of prophylactic antibiotic use (rational and irrational) in relation to body temperature and LOS in cesarean section patients at a hospital in Malang City. Keywords: Cesarean Section, ATC/DD, DU 90%, Gyssens, Rationality